THE ROLE OF ENGLISH SPEAKING CLUB IN ENHANCING STUDENT’S GRAMMAR AT HAMZANWADI UNIVERSITY - Qistina, Siti Atiqah; Ari Prasetyaningrum; Astrid Dwimaulani; M. Adib Nazri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores the role of the English Speaking Club (ESC) at Hamzanwadi University in enhancing students' grammar mastery through a non-formal, collaborative environment. While conventional EFL classrooms often focus on explicit form-based instruction that triggers cognitive overload, informal spaces offer a low-anxiety alternative. Employing a qualitative case study approach, data were gathered through participant observations and in-depth interviews with active ESC members, then analyzed using thematic analysis. The findings reveal two primary mechanisms: first, the informal environment significantly reduces speaking anxiety, aligning with Krashen's Affective Filter Hypothesis; second, peer interactions facilitate spontaneous error correction, acting as peer scaffolding that accelerates the transition from declarative grammatical knowledge to procedural fluency, as posited by Vygotsky’s Sociocultural Theory. This study contributes theoretically by bridging cognitive Second Language Acquisition (SLA) with sociocultural frameworks and practically by urging higher education institutions to integrate extracurricular language clubs into comprehensive language learning ecosystems.